Pemanfaatan Kedelai Sebagai Bahan lokal menjadi Tempe di Desa Ketapang Indah, Singkil Utara - Syafiq, M Rizki; Elyanda, Boy; Marnisa, Sella; Aula, Sri Ruhama; Fadhillah, Risa; Chairunnisa, Cut; Aminah, Siti; Nasution, Aswin; Farisi, Nurcholis Al (Universitas Teuku Umar, 2025)
Ketapang Indah village is located in North Singkil sub-district, Aceh Singkil district. Due to its position close to the coast, influenced by sea breezes and weather conditions that tend to be humid. The main focus of this occation is the utilization of local materials in the form of processing food ingredients into tempeh. Tempeh is a fermented soybean product that is a source of high-quality vegetable protein and has various health benefits. This service aims to explore the utilization of local materials in making tempe, including a basic understanding of tempe. The process of making tempeh involves several stages, from soaking, cooking, inoculation with yeast, to fermentation. This service also discusses the importance of counseling the community on how to make tempeh and its benefits to increase product diversity and support the local economy. The service method used in this activity is a combination of counseling (lecture) with hands-on practice.